Augmented efficacy of nano-formulated docetaxel plus curcumin in orthotopic models of neuroblastoma. (February 2023) - Di Francesco, Martina; Pastorino, Fabio; Ferreira, Miguel; Fragassi, Agnese; Di Francesco, Valentina; Palange, Anna Lisa; Celia, Christian; Di Marzio, Luisa; Cilli, Michele; Bensa, Veronica; Ponzoni, Mirco; Decuzzi, Paolo
Abstract: Neuroblastoma is a biologically heterogeneous extracranial tumor, derived from the sympathetic nervous system, that affects most often the pediatric population. Therapeutic strategies relying on aggressive chemotherapy, surgery, radiotherapy, and immunotherapy have a negative outcome in advanced or recurrent disease. Here, spherical polymeric nanomedicines (SPN) are engineered to co-deliver a potent combination therapy, including the cytotoxic docetaxel (DTXL) and the natural wide-spectrum anti-inflammatory curcumin (CURC). Using an oil-in-water emulsion/solvent evaporation technique, four SPN configurations were engineered depending on the therapeutic payload and characterized for their physico-chemical and pharmacological properties. All SPN configurations presented a hydrodynamic diameter of ∼ 185 nm with a narrow size distribution. A biphasic release profile was observed for all the configurations, with almost 90 % of the total drug mass released within the first 24 h. SPN cytotoxic potential was assessed on a panel of human neuroblastoma cells, returning IC50 values in the order of 1 nM at 72 h and documenting a strong synergism between CURC and DTXL. Therapeutic efficacy was tested in a clinically relevant orthotopic model of neuroblastoma, following the injection of SH-SY5Y-Luc + cells in the left adrenal gland of athymic mice. Although ∼ 2 % of the injected SPN per mass tissue reached the tumor, the overall survival of mice treated with CURC/DTXL–SPN was extended by 50 % and 25 % as compared to the untreated control and the monotherapies, respectively. In conclusion, these results demonstrate that the therapeutic potential of the DTXL/CURC combination can be fully exploited only by reformulating these two compounds into systemically injectable nanoparticles. Graphical Abstract: ga1